ROLE OF SIMS IN THE INDUSTRY OF GOJEK COMPANY ONLINE DOSEN - Faeni, Dewi Puspaningtyas; Rahmawati , Putri Salsabilla (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Technological progress continues to progress, becoming an inevitable part of life in line with the advances of science. The innovations born out of these advances provide considerable benefits, providing a variety of new facilities and methods in everyday activities. Especially in the field of technology, society benefits greatly from these innovations, thus simplifying everyday tasks such as communication. In ancient times, people relied on natural things to communicate, like bells, signals, but with the advancement of the times, communication tools like cell phones have evolved so that we can send messages easily without the control of space and time. The same goes for Internet technology, which is increasingly making it easier to access information quickly, both domestically and internationally. Besides, social networks, one form of information technology, enable us to keep track of the activities and information of friends, thus being easily accessible and providing enormous benefits.